Germany : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
This 2012 Article IV Consultation reports that the German economy's performance has been remarkable despite facing considerable headwinds. Several conditions are now in place in Germany for a domestic demand-led recovery. Employment creation has been robust and unemployment at 5.3 percent is at a postreunification low. Executive Directors have commended Germany's strong macroeconomic management, which has resulted in a favorable economic performance despite the uncertain external environment. Directors have underscored Germany's pivotal role in reducing euro area and global imbalances.